2003
DOI: 10.1542/peds.112.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Posture on Oxygenation, Lung Volume, and Respiratory Mechanics in Premature Infants Studied Before Discharge

Abstract: Superior oxygenation in the prone posture in oxygen-dependent premature infants studied before discharge could be explained by higher lung volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 14 publications
5
62
0
1
Order By: Relevance
“…Many infants on noninvasive support are placed in the prone position as previous studies have demonstrated that this reduces thoraco-abdominal asynchrony, improves oxygenation and increases functional residual capacity (5,7,24). Our study also shows an increase in EELV when switching from supine to prone position but adds important information on its regional distributions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many infants on noninvasive support are placed in the prone position as previous studies have demonstrated that this reduces thoraco-abdominal asynchrony, improves oxygenation and increases functional residual capacity (5,7,24). Our study also shows an increase in EELV when switching from supine to prone position but adds important information on its regional distributions.…”
Section: Discussionmentioning
confidence: 99%
“…To make these transitions successful, infants should be able to maintain an optimal EELV and normal ventilation during nCPAP. Placing infants in prone position might facilitate this transition to nCPAP as this posture seems to increase EELV and improve respiratory mechanics (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…To minimize the invasiveness of this study, pulmonary function measurements were made in the body position also determined by the clinical care provider. As previous data in preterm infants prior to discharge have shown that respiratory mechanics are not affected by body position, 25 it is unlikely that this is a contributing confounder.…”
Section: Discussionmentioning
confidence: 82%
“…In other studies, the indicator that most improved oxygenation and oxygen saturation and reduced hypoxia was the prone position, thus promoting its use in newborns 6,[18][19][20][21] . Our results show that the elastic chest band had a strong influence on oxygen saturation.…”
Section: Variablesmentioning
confidence: 97%